(untitled) (Jurnal Ipteks Terapan, 2023)
The aim of this research is to examine the effect of financial distress on Management Change, growth company, Size HOOD, And opinion audit of voluntary auditor switching changes in manufacturing companies listed on the Indonesian Stock Exchange (BEI) for the 2019-2022 period. Secondary data comes from financial reports Which published by market capital in Indonesia stock exchange. The type of research used in this research is testing hypotheses, using a purposive sampling method. There are 44 data samples used as research objects. This research uses regression analysis logistics for testing hypotheses. The research results show that financial distress, management changes, company growth, KAP size, have no effect on Voluntary Auditor Switching while Audit Opinion has an effect on Auditor Switching Voluntary. It is known from the SPSS test that the value is 0.000<0.05. Meanwhile, simultaneously, the variables Financial Distress, Management Change, Company Growth, KAP Size, and Auditor Opinion influence Voluntary Auditor Switching